Blood–spinal cord barrier breakdown and pericyte deficiency in peripheral neuropathy. Issue 1 (28th July 2017) - Sauer, Reine‐Solange; Kirchner, Juliane; Yang, Shaobing; Hu, Liu; Leinders, Mathias; Sommer, Claudia; Brack, Alexander; Rittner, Heike L.
Abstract: The blood–spinal cord barrier (BSCB) prevents leakage of molecules, such as pronociceptive mediators, into the spinal cord, but its role in the pathophysiology of neuropathic pain is not completely understood. Rats with chronic constriction injury (CCI) develop mechanical allodynia, thermal hypersensitivity, and reduced motor performance (Rota‐Rod test) compared with sham‐injured mice—similar to mice with spared nerve injury (SNI). The BSCB becomes permeable for small and large tracers 1 day after nerve ligation. Messenger RNA (mRNA) expression of tight junction proteins (TJPs) occludin, claudin‐1, claudin‐5, claudin‐19, tricellulin, and ZO‐1 significantly declines 7–14 days after CCI or SNI. ZO‐1 and occludin are reduced in the cell membrane. In capillaries isolated from the spinal cord, immunoreactivity of claudin‐5 and ZO‐1 is fainter. In parallel, the number of platelet‐derived growth factor receptor β (PDGF‐β) + and CD13 + pericytes in the spinal cord drops. Reduced levels of cytosolic transcription factors like β‐catenin, but not SMAD4 and SLUG, could account for reduced TJP mRNA. In summary, neuropathy‐induced allodynia/hypersensitivity is accompanied by a loss of pericytes in the spinal cord and a leaky BSCB. A better understanding of these pathways and mechanisms in neuropathic pain might foster the design of novel treatments to maintain spinal cord homeostasis.